La(III) and Ce(IV)Complexes of Novel Azo-Theophylline Ligand :Structural Analysis and Biological Effectiveness - Manulla, Mohnned Hamady; Abbas, Alyaa Khider (Iraqi Journal of Science, 2025)
A novel compound, 8-[(E)-(3-hydroxyphenyl)diazenyl]-1,3-dimethyl-3,7-dihydro-1H-purine-2,6-dione (PAT), was synthesized via the diazotization and coupling reaction of m-amino phenol with theophylline. In addition, complexes of the ligand (PAT) with [Ce (IV) and La (III)] were synthesized. The structural features of the synthesized compounds were examined using several spectroscopic techniques including elemental analyses [CHN], Fourier transform infrared spectroscopy (FTIR), UV-Visible spectroscopy (UV-Vis) and proton nuclear magnetic resonance spectroscopy (1H NMR). Other characterization techniques employed were magnetic measurement, molar conductance data, thermal analysis (thermogravimetric analysis, TGA), inductive coupled plasma (ICP), and scanning electron microscopy (SEM). Through the FTIR study, it was found that the PAT ligand behaves as a neutral N,N- bidentate ligand and that the two complexes have octahedral coordination geometry with six coordination sites. The ligand and its complexes were assessed as antioxidant by DPPH free radical scavenging with ascorbic acid as a positive control for comparative with the synthesized compounds which were appeared good activities, also all compounds were tested for their antibacterial activity via disk diffusion method (MIC) at two concentration (50 mg/ml and 100 mg/mol) they had varying effectiveness compared to amoxicillin as reference